2019
DOI: 10.1590/rbz4820180222
|View full text |Cite
|
Sign up to set email alerts
|

Production and quality of the silage of corn intercropped with Paiaguas palisadegrass in different forage systems and maturity stages

Abstract: The objective of this study was to evaluate dry matter production, fermentative parameters, and nutritional value of the silage of corn intercropped with Paiaguas palisadegrass in different forage systems and maturity stages, in the off-season. The experiment was carried out in a randomized block design, with four replications, in a 5×3 factorial arrangement consisting of five forage systems: corn monocropped; Paiaguas palisadegrass monocropped; corn intercropped with Paiaguas palisadegrass in the row, inter-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…The increase in the proportion of forage in silage also resulted in higher values for the buffering capacity (Figure 1b), showing a linear increase up to the maximum dose of forage. This occurred because tropical forages have a higher buffering capacity than annual crops (Souza et al, 2019). According to S. S. Oliveira et al (2020), forage grasses have a high buffering capacity and a low content of soluble carbohydrates; this can influence pH values, as observed in this study.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…The increase in the proportion of forage in silage also resulted in higher values for the buffering capacity (Figure 1b), showing a linear increase up to the maximum dose of forage. This occurred because tropical forages have a higher buffering capacity than annual crops (Souza et al, 2019). According to S. S. Oliveira et al (2020), forage grasses have a high buffering capacity and a low content of soluble carbohydrates; this can influence pH values, as observed in this study.…”
Section: Resultsmentioning
confidence: 50%
“…Between the two forage silages, the 100% Paiaguas palisadegrass silage had a 12% higher crude protein than the 100% Ipypora grass silage. This was due to the morphological structure of Paiaguas palisadegrass, which has a high leaf:stem ratio than Ipypora grass and thus generates better-quality forage (Epifanio et al, 2019;Souza et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, the lowest production of DM was obtained by Paiaguas palisadegrass monocropped forage system, demonstrating that the intercropping has contributed for the rise of DM production in 110.6; 127.9 and 48.9%, in the rows, inter-rows and oversown intercropped, respectively. Several studies have evidenced the benefits of producing silages from intercropping systems (Ribeiro et al, 2017;Cruvinel et al, 2017;Souza et al, 2019;Oliveira et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…BRS Paiaguas is a great option, the plant attends all the requirements needed in different systems of production, encompassing different technological levels (Costa et al, 2016). Besides that, the forage has been used for the production of silage in integrated systems, allowing great results (Santos et al, 2016;Costa et al, 2018;Souza et al, 2019;Oliveira et al, 2020). Cruvinel et al (2017) reported that the silage of additive sunflowers with tropical forages are able to bring great benefits to the quality of the silage, for example, decrease in the content of ethereal extract, in the fibers of acid detergents, lignin, in addition to the production of silage in the off season, with good quality and with sufficient amount for nutritional maintenance of ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…The consortium with sorghum did not positively influence the fraction of CP, because the highest values were recorded in maize monocultures (Agri 340 and Agri 320), also presenting the highest estimates of TDN (62.41%) in relation to other cultivation systems (Table 2). Regarding EE it is possible to observe an average value of 2.14% for cultivation systems (Table 2), these low estimates of EE often observed in C 4 grasses (Souza et al, 2019).…”
Section: Nutritive Value Of Silage In Cultivation Systemsmentioning
confidence: 87%